Pengaruh Financial Knowledge Dan Locus Control Terhadap Financial Management Behavior Mahasiswa Tingkat Akhir Jurusan Akuntansi Universitas Bina Bangsa - Raden Irna Afriani; Rika Kartika (Sains: Jurnal Manajemen dan Bisnis, 2021)
This study aims to know influence to analyze and financial knowledge to financial management behavior and to analyze and know influence locus of control to financial management behavior. This study used quantitative descriptive, both primary data. Technique collection data using a questionnaire and engineering use square minimal partial data analysis ( pls ). Objects in this research, university students of the end of the year  2020-2021. Technique the sample use random sampling, with as many as the total sample obtained 76 respondents. This research result indicates that financial knowledge and locus of control influence financial management behavior.